2009
DOI: 10.1186/1471-2431-9-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of broad range 16S rDNA PCR and conventional blood culture for diagnosis of sepsis in the newborn: a case control study

Abstract: Background: Early onset bacterial sepsis is a feared complication of the newborn. A large proportion of infants admitted to the Neonatal Intensive Care Unit (NICU) for suspected sepsis receive treatment with potent systemic antibiotics while a diagnostic workup is in progress. The gold standard for detecting bacterial sepsis is blood culture. However, as pathogens in blood cultures are only detected in approximately 25% of patients, the sensitivity of blood culture is suspected to be low. Therefore, the diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(98 citation statements)
references
References 30 publications
3
92
1
2
Order By: Relevance
“…The diagnostic performances of these in-house assays varied considerably (for a review, see reference 18). For instance, in a study with 48 newborns admitted to the ICU with suspected sepsis, the PCR detection assay with sequencing of a limited number of samples revealed a diagnostic sensitivity of 66.7% and a specificity of 87.5% (26). In another study, PCR and hybridization probes differentiating between gram-positive and gram-negative taxons to detect bacteremia in 548 blood samples from newborns (14) resulted in a sensitivity and specificity of 96 and 99.4%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic performances of these in-house assays varied considerably (for a review, see reference 18). For instance, in a study with 48 newborns admitted to the ICU with suspected sepsis, the PCR detection assay with sequencing of a limited number of samples revealed a diagnostic sensitivity of 66.7% and a specificity of 87.5% (26). In another study, PCR and hybridization probes differentiating between gram-positive and gram-negative taxons to detect bacteremia in 548 blood samples from newborns (14) resulted in a sensitivity and specificity of 96 and 99.4%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…were the most frequently detected. In a cohort of newborns with sepsis, other authors evaluated amplification of the bacterial 16S rRNA gene for the early diagnosis of bloodstream infection: compared to blood culture, the sensitivity was 66.7% and the specificity was 87.5% (19). These percentages are markedly lower than the 85% and 93.5%, respectively, that we observed in the present study for the SeptiFast test compared to blood culture, reinforcing the evidence of its higher performance than previous PCR-based methods.…”
Section: Discussionmentioning
confidence: 99%
“…In order to estimate the true concentration of pathogen DNA available in whole blood for molecular analysis from patients with bloodstream infections, we analyzed the data available in the literature. Organism-specific quantitative PCR has been used to measure the bacterial DNA present in whole-blood specimens from patients with sepsis, pneumonia, or suspected bloodstream infections (13,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). Each of these studies analyzed whole-blood specimens from patients with suspected or confirmed infections rather than spiked samples for which the genome-to-viable cell ratio is expected to be close to 1:1.…”
Section: Repeated Analytical Testing By Pcr/esi-msmentioning
confidence: 99%